Season of delivery and risk of venous thromboembolism during hospitalization among pregnant women - Qian Li; Hongfei Wang; Huafang Wang; Jun Deng; Zhipeng Cheng; Wenyi Lin; Ruiqi Zhu; Shi Chen; Jinrong Guo; Huarong Li; Yong Chen; Xiaowei Yuan; et al. (Frontiers Media S.A., 2023)
BackgroundSeasons were found to be related to the occurrences of venous thromboembolism (VTE) in hospitalized patients. No previous study has explored whether seasons were associated with VTE risk in pregnant women. This study aimed to investigate the relationships between the season of delivery and VTE risk during hospitalization among pregnant women.MethodsThis is a multi-center retrospective cohort study of pregnant women. Participants were those who delivered at seven designated sites in Hubei Province, China, during the period from January 2017 to December 2022. They were categorized according to their season/month of delivery. Information on new-onset VTE during hospitalization was followed.ResultsApproximately 0.28% (104/37,778) of the pregnant women developed new-onset VTE during hospitalization for delivery. After adjustment, compared with participants in the spring group, participants in the summer, autumn, and winter groups had an increased risk of VTE during hospitalization. The ORs were 2.59 [1.30, 5.15], 2.83 [1.43, 5.60], and 2.35 [1.17, 4.75] for the summer, autumn, and winter groups, respectively. Pregnant women in the combined group (summer + autumn + winter) had an increased risk of VTE during hospitalization than those in the spring group (OR, 2.59 [1.39, 4.85]). By restricting the analyses among pregnant women without in vitro fertilization, gestational diabetes mellitus, and preterm, the results still remained robust. Compared with participants who delivered in March, April, and May, participants who delivered in June, July, September, November, December, and February had a higher risk of VTE during hospitalization.ConclusionThis study demonstrated that pregnant women who delivered in summer, autumn, and winter had an increased VTE risk during hospitalization compared with those who delivered in spring.